Análise do comportamento discricionário do gestor sob a ótica da teoria do prospecto e do excesso de confiança - Nascimento, Ariane Firmeza Mota (2020)
The work aims to verify the behavior of earnings management in terms of behavioral finance, specifically the Prospect Theory and overconfidence - in order to identify the tendency to opportunistic manipulation. Through discretionary accruals and operational decisions, the levels - moderate and aggressive - of manipulating accounting results were verified. The sample is composed of firms listed in the Brazilian and North American capital markets, in the period from 2010 to 2018. As a metric of earnings management, Dechow et. al (2012), the manipulation of operational decisions was identified according to Roychowdhury (2006). These three metrics of earnings management by actual activities have been combined into a single aggregate metric that corresponds to the sum of abnormal levels of cash flow, discretionary expenses and production costs. The gains and losses on the return of the shares and the manager's predisposition to risk were used to analyze the perspective of the Prospect Theory, which establishes an asymmetric relationship between the behavior of individuals in relation to gains and losses in risk situations. The predisposition of the manager to risk - to manage accounting results - was analyzed through the indicators of global governance, since these indicators reflect the people’s perception and tend to lead actions in relation to the public and private initiative. On the other hand, managers' overconfidence was verified, which can redirect what the Prospectus Theory advocates. The metric used for this was the exercise of stock options by managers, according to Malmendier and Tate (2005). Through the techniques of multiple and quantile regression, the effect of these measures on the various levels of earnings management was verified. In general, the results indicate that, in the Brazilian environment, the behavior of the manager in earnings management is consistent with what the Prospectus Theory advocates, since in the face of gains, managers manipulate the results in a moderate way and in the face of losses, aggressively. Managers demonstrate a risk predisposition as regulatory quality positively influences the more aggressive levels of discretionary accruals. In the North American environment, earnings management by accruals was moderately influenced by gains in share returns and losses did not influence the aggressive levels of discretionary accruals. On the other hand, manipulation by real activities is aggressive when managers face losses in the financial market. When they experience gains, they prefer to manipulate operating activities, in a moderate way, through cash flows and production costs. Above all, the asymmetric relationship, foreseen in the theory of prospects, for the manipulation of operating activities through cash flows and production costs is undone, demonstrating that the managers' overconfidence can lead the manager to earnings management in a opportunistic in this modality. From the perspective of the Prospect Theory, emphasis is placed on the opposition of the economic concepts that individuals must risk while gaining and must be opposed when they experience losses, in order to identify the tendency to opportunistic earnings management.